2018
DOI: 10.4183/aeb.2018.49
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Cobalamin Deficiency Symptoms Related to Long-Term Metformin Use in T2dm Patients

Abstract: Background. Metformin is the first-line oral antidiabetic agent used in the treatment of diabetes mellitus. One of the adverse reactions of the long term use of metformin is cobalamin malabsorption. Clinical and laboratory findings are important in the diagnosis of cobalamin deficiency.Objective. This study aimed to evaluate the risk of cobalamin deficiency symptoms related to long-term use of metformin in type 2 diabetes mellitus patients at Pasar Rebo General Hospital in Jakarta.Setting. This quantitative, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…8 Studies have reported conflicting findings regarding the consequences of vitamin B12 deficiency in T2DM patients. 6,10,11 Hendrawati et al reported higher proportions of neuropathy symptoms and haematologic abnormalities among patients who took metformin for a longer period of time (>3 years versus 1-3 years). 11 Aroda et al 's large cohort study of 2,155 participants found a higher prevalence of neuropathy and anaemia in the metformin group compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Studies have reported conflicting findings regarding the consequences of vitamin B12 deficiency in T2DM patients. 6,10,11 Hendrawati et al reported higher proportions of neuropathy symptoms and haematologic abnormalities among patients who took metformin for a longer period of time (>3 years versus 1-3 years). 11 Aroda et al 's large cohort study of 2,155 participants found a higher prevalence of neuropathy and anaemia in the metformin group compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,11 Hendrawati et al reported higher proportions of neuropathy symptoms and haematologic abnormalities among patients who took metformin for a longer period of time (>3 years versus 1-3 years). 11 Aroda et al 's large cohort study of 2,155 participants found a higher prevalence of neuropathy and anaemia in the metformin group compared to the placebo group. 6 On the other hand, Alharbi et al 's study found no significant differences in the prevalence of peripheral neuropathy between metformin users and non-metformin users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, investigations of inflammation markers other than CRP such as IL-2 and TNF-α may help to clarify the pathogenesis of the relationship between red blood cell indices and inflammation. Third, we could not evaluate the body mass index of the patients, the history of smoking and the history of metformin usage, due to retrospective design of the study (28,29). These factors could have affected the RDW values.…”
Section: Discussionmentioning
confidence: 99%
“…22 Proposed mechanisms to explain metformin induced vitamin B12 deficiency among T2DM patients include: alterations in small bowel motility, competitive inhibition or inactivation of vitamin B12 absorption, alterations in intrinsic factor (IF) levels, interaction with the cubulin endocytic receptor and inhibition of calcium dependent absorption of vitamin B12-IF complex at the terminal ileum. [23][24][25]…”
Section: Introductionmentioning
confidence: 99%